Download presentation

Presentation is loading. Please wait.

Published byOwen Chapman Modified over 2 years ago

1
(a + b) 2 = a 2 + 2ab + b 2 a a a2a2 b ab b2b2 b b b a a a + b (a + b ) 2 = a2a2 +ab +b 2 = a 2 + 2ab + b 2

2
a b b a a b (a – b) 2 ab – b 2 b 2 a-b a2a2 (a-b) 2 = a 2 -(ab-b 2 )-(ab-b 2 )-b 2 = a 2 -ab+b 2 -ab+b 2 -b 2 = a 2 -2ab+b 2

3
(a + b) (a - b) = a 2 - b 2 a a-b a 2 - ab b ab ab-b 2 b2b2 b b b a a-b a a + b (a+b)a 2 – ab+ab – b 2 = a 2 - b 2 (a-b) =

4
(x + a)(x + b ) = x 2 + (a + b)x + ab x x x2x2 a ax bx ab b a b x x x + a x + b ( x + a ) x2x2 +ax +bx+ab = x 2 – (a +b )x +ab (x + b) =

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google